Identifikasi Aktivitas Penggunaan Pestisida Kimia yang Berisiko pada Kesehatan Petani Hortikultura - Ilyas Ibrahim; Sahrir Sillehu (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2022)
The purpose of this study is to identify the activities of farmers using pesticides that pose a risk to the health of farmers in the agricultural area of Larangan village. This type of research is descriptive quantitative research with a cross-sectional study design. The samples taken were 67 respondents based on the inclusion criteria, namely actively spraying chemical pesticides and a minimum working period of 25 years. The data collection instrument used a questionnaire and data analysis using SPSS tools to describe the activities of farmers using pesticides. The results showed that activities that were at risk of being exposed to chemical pesticides were not using the correct personal protective equipment, mixing pesticides without using gloves, spraying against the wind, spraying while smoking cigarettes, mixing several types of pesticides with excessive doses when spraying was carried out during the day. Health complaints felt by farmers included shortness of breath, headaches, nausea and vomiting, diarrhea, skin diseases, muscle disorders, blurred vision. Farmers' activities do not follow the procedures for using pesticides, which pose a risk to health. Suggestion; farmers must use chemical pesticides wisely according to the specified standards and must be equipped with knowledge about how to use pesticides correctly and their negative health impacts.Keywords: identification, farmer activities, pesticides, agriculture